Percepción docente sobre el uso de Educaplay como herramienta de evaluación en la carrera de Pedagogía de la Actividad Física y Deporte de la Universidad Nacional De Loja, 2024 - Nivelo Cabrera, Carlos Antonio (2025)
This curricular integration project analyzed teachers' perceptions of using Educaplay as an evaluation tool in the Physical Activity and Sports Pedagogy course at the National University of Loja. The study employed a mixed-methods approach, descriptive in nature, with a nonexperimental, cross-sectional research design. A survey was utilized as the primary research technique, targeting a sample of 12 teachers selected based on inclusion and exclusion criteria. Key findings reveal that 50% of the participating teachers have over 10 years of experience in higher education, 67% incorporate ICT in their teaching practices, and 35% frequently use virtual environments. This highlights a prevalent adoption of new technologies focused on interaction, communication, and collaboration, but also underscores inconsistencies in the evaluation techniques and tools currently employed. In response to this situation and the expressed willingness of teachers to adopt innovative approaches, a didactic manual was developed. This manual provides step-by-step instructions on how to access the Educaplay platform, create and publish activities, and retrieve records of student performance. The study concludes that teachers positively perceive ICT usage in higher education, particularly for evaluation purposes. The proposed manual represents a practical resource for enhancing and innovating the evaluation processes within the Physical Activity and Sports Pedagogy course